Poverty and Youth Vulnerability to Cybercrime in Nigeria: A Case of Ikorodu, Lagos. (2015-2023) - Mabel Chinonso Fredick; Samuel Sunday Idowu; Chioma Anioke; Babajide Adelayo; Tunmise Daramola (Universitas Medan Area, 2025)
Background: Many countries are leveraging the strength of the youth population to advance their socio-economic development, while the internet, exploited mostly by the age bracket, is one of the most lucrative platforms for businesses and social transactions across the world today. However, it is fast becoming the safest avenue for cybercrime thriving in Nigeria, largely perpetrated by the youth population and underscored chiefly by a high level of poverty as the push factor. Aim: The study's overarching objective is to investigate how poverty has contributed to the youth's vulnerability to committing cybercrime in the Ikorodu local government of Lagos State, Nigeria, between 2015-2023. Method: The study adopts a descriptive survey design to analyze the retrieved 251 questionnaires out of 399 administered to youth in the Ikorodu local government of Lagos state via a cluster sampling technique. Findings: The findings reveal that youths' limited access to economic opportunities, socio-economic inequalities, and lack of cybercrime awareness are core contributors to their impoverishment, heightening their susceptibility to indulge in cybercrimes. Conclusion: The research concluded that poverty largely contributed to youth vulnerability to cybercrimes in Ikorodu, Lagos, Nigeria.